2021
DOI: 10.1093/cercor/bhab154
|View full text |Cite
|
Sign up to set email alerts
|

Lost Dynamics and the Dynamics of Loss: Longitudinal Compression of Brain Signal Variability is Coupled with Declines in Functional Integration and Cognitive Performance

Abstract: Reduced moment-to-moment blood oxygen level-dependent (BOLD) signal variability has been consistently linked to advanced age and poorer cognitive performance, showing potential as a functional marker of brain aging. To date, however, this promise has rested exclusively on cross-sectional comparisons. In a sample of 74 healthy adults, we provide the first longitudinal evidence linking individual differences in BOLD variability, age, and performance across multiple cognitive domains over an average period of 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 112 publications
2
21
2
Order By: Relevance
“…We also found that working memory load-based upregulation of "local" signal variability was tightly coupled with increased functional integration within every network examined. This provides first human evidence that local dynamics and functional integration are closely aligned outside of the resting-state 20,21 . Crucially, striato-thalamic functional integration uniquely accounted for a sizable proportion of ΔSDBOLD in every network, but functional integration in non-striato-thalamic networks was not independently associated with modulation of striato-thalamic SDBOLD.…”
Section: As the Brain To Fluctuates Under Load The Striatothalamic Sy...mentioning
confidence: 70%
See 3 more Smart Citations
“…We also found that working memory load-based upregulation of "local" signal variability was tightly coupled with increased functional integration within every network examined. This provides first human evidence that local dynamics and functional integration are closely aligned outside of the resting-state 20,21 . Crucially, striato-thalamic functional integration uniquely accounted for a sizable proportion of ΔSDBOLD in every network, but functional integration in non-striato-thalamic networks was not independently associated with modulation of striato-thalamic SDBOLD.…”
Section: As the Brain To Fluctuates Under Load The Striatothalamic Sy...mentioning
confidence: 70%
“…In the present study, we test for unique associations between brain signal variability regulation and our three research targets (D2 capacity, functional integration, and decisionmaking; Figure 1), specifically within the domain of working memory. Neural variability has proven highly responsive to working memory demands 5,7,10,32,33 , dopamine levels 5,10,12 , and the striato-thalamic system in general 5,20,21,32 . However, it is not yet known whether one's capacity to regulate neural variability in the face of varying working memory load is associated with any of our research targets.…”
Section: The Current Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Although FC and SD measures are different yet complimentary features for brain functional characterization, SD BOLD has been shown to be a more sensitive parameter for detecting subtle brain changes in aging studies, and it is therefore more appropriate for characterization of the CRCI in long-term older cancer survivors. Garrett et al showed that SD BOLD was coupled with dynamic functional integration and cognitive performance in aging [ 18 ]. They found that the SD BOLD trajectory followed an inverted U-shape across the lifespan, i.e., from low variability in infancy, to high variability in young adulthood to lower variability in older adulthood [ 19 ].…”
Section: Introductionmentioning
confidence: 99%